2012
DOI: 10.3176/lu.2012.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Evidentiality in ­Livonian

Abstract: The study focuses on dedicated grammatical evidentials and evidentiality strategies in the two main dialects of Livonian -Courland and Salaca Livonian. The analysis of Livonian evidentiality is based on a model originally proposed by Rätsep (1971) for Estonian, which posits two subsystems of reported evidentiality -the reported indicative (oblique mood) and the reported imperative (jussive).The study shows that evidentiality in Livonian -despite the intense and longlasting contacts of this language with Latvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The oblique mood, for instance, used to mark indirectly reported information, both Salaca and Courland Livonian have employed forms ending in -ji, similar to the nomen agentis forms, e.g. Sal and Cour ta tēji 'he/she does (reported evidentiality)' (see Kehayov et al 2012). Oblique mood forms resembling the nomen agentis forms are also found in the Hääde-meeste variety of Estonian, geographically a close neighbor of Salaca Livonian.…”
Section: Salaca and Courland Livonian Inflectional Morphologymentioning
confidence: 99%
“…The oblique mood, for instance, used to mark indirectly reported information, both Salaca and Courland Livonian have employed forms ending in -ji, similar to the nomen agentis forms, e.g. Sal and Cour ta tēji 'he/she does (reported evidentiality)' (see Kehayov et al 2012). Oblique mood forms resembling the nomen agentis forms are also found in the Hääde-meeste variety of Estonian, geographically a close neighbor of Salaca Livonian.…”
Section: Salaca and Courland Livonian Inflectional Morphologymentioning
confidence: 99%
“…In the religious literature of the 20th century, jussive forms also are found. The jussive is used for conveying a) obligation (11), b) concession, c) a desire or order for the hearer to mediate the original wish, order, or prohibition; these forms are accompanied by the particle la'z, as seen in examples (11) (Viitso 2008: 320) The use of the jussive in reported speech and commands (example 12) is discussed in a separate study by Kehayov et al (2012), who also draw parallels between the expression of indirect commands and wishes in Estonian and Livonian. As they point out, where Livonian uses the jussive, Estonian typically uses the conditional mood (Kehayov et al 2012: 50).…”
Section: Mood and Modalitymentioning
confidence: 99%
“…Klaas-Lang and Norvik (2014: 600-603) also use the term evidentiality, when comparing the various ways for conveying evidentiality in the Baltic region. Kehayov et al (2012) distinguish between the reported indicative and the reported imperative (jussive). The main task of the reported indicative is to show that the speaker is only a mediator and not responsible for the message, see example (14).…”
Section: Mood and Modalitymentioning
confidence: 99%
See 2 more Smart Citations